2005
DOI: 10.1200/jco.2005.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Peripheral Blood Stem-Cell Compared With Bone Marrow Transplantation in the Management of Hematologic Malignancies: An Individual Patient Data Meta-Analysis of Nine Randomized Trials

Abstract: Purpose-Considerable uncertainty exists regarding relative effects of allogeneic peripheral blood stem cells transplantation (PBSCT) versus bone marrow transplantation (BMT) on outcomes of patients with hematologic malignancies.Patients and Methods-To provide the totality of research evidence related to the effects of PBSCT versus BMT, we conducted an individual-patient data meta-analysis using data from nine randomized trials enrolling 1,111 adult patients. Results-Compared with BMT, PBSCT led to faster neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(56 citation statements)
references
References 39 publications
(14 reference statements)
3
52
0
1
Order By: Relevance
“…Support for this shift has come from numerous large, multicenter, randomized trials performed to-date, which have collectively shown that engraftment/reconstitution is often faster and more robust with mPB than with marrow, and may be associated with a decreased relapse rate, but this appears to depend upon the patient population and malignancy in question [125, 126]. However, as originally feared, these studies have also revealed that the use of mPB is associated with a significantly higher rate of chronic (and perhaps acute) GVHD than marrow, and offers no significant improvement in survival [114, 115, 124, 127137].…”
Section: Alternate Sources Of Hscmentioning
confidence: 99%
“…Support for this shift has come from numerous large, multicenter, randomized trials performed to-date, which have collectively shown that engraftment/reconstitution is often faster and more robust with mPB than with marrow, and may be associated with a decreased relapse rate, but this appears to depend upon the patient population and malignancy in question [125, 126]. However, as originally feared, these studies have also revealed that the use of mPB is associated with a significantly higher rate of chronic (and perhaps acute) GVHD than marrow, and offers no significant improvement in survival [114, 115, 124, 127137].…”
Section: Alternate Sources Of Hscmentioning
confidence: 99%
“…These data suggest the deleterious effect iron overload has on transplant outcome may be overcome by aggressive post-transplant phlebotomy in these types of patients. Numerous studies have clearly defined an increased risk of chronic-GVHD with the use of PBPC compared to BM [19,47,48]. Although highly successful in preventing graft-failure, this transplant approach led to a high incidence of chronic-GVHD [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell source is one of the main factors affecting engraftment kinetics [18,[23][24][25]. As example in one large study assessing the impact of graft source on unrelated donor allo-HCT in adults with acute leukemia, median times to neutrophil (defined as achievement of an absolute neutrophil count of ≥500 cells/mm 3 for 3 consecutive days) and platelet (defined as achievement of ≥20,000 platelets/mm 3 unsupported by transfusion for 7 days) recoveries were 14 (range, 5-28) and 19 (range, 7-112) days respectively after peripheral blood stem cell transplantation (PBSCT), 19 (range 6-41) and 28 (range, 10-150) days respectively after bone marrow transplantation, and 24 (range, 12-68) and 52 (range, 22-275) days, respectively after UCBT [18].…”
Section: Factors Affecting Hematologic Recovery After Allo-hctmentioning
confidence: 99%